EVALUATION OF ADDING TWO TYPES OF ORGANIC CHROMIUM ON ENHANCING GROWTH AND CHEMICAL COMPOSITION CRITERIA OF COMMON CARP Cyprinus carpio L. - Alaa Alkhaledy; Mahmoud Mohammad (Mesopotamia Journal of Agriculture)
The study aims to indicate the effect of two types of organic chromium added on growth criteria, namely chromium picolinate, at an amount of 0.3, 0.4, and 0.5 mg/kg feed (T2, T3, and T4), and 0.3, 0.4, and 0.5 mg/kg feed of chromium nicotinate (T5, T6, and T7), besides the standard diet without additives (T1). Results of the statistical analysis showed that T4 and T7 were significantly superior (P≤ 0.05) in the criteria of final weight, total weight gain, daily growth rate, relative growth rate, specific growth rate, food intake, feed conversion ratio, and feed efficiency ratio over all other experimental treatments, including standard diet. Results of the protein retention and protein productive value criteria showed that T2 and T3 were significantly superior to the remaining experimental therapies. At the same time, T4 and T7 were significantly superior to the remaining experimental treatments in the protein efficiency ratio. The fish-fed diets T1, T3, T4, and T7 outperformed the other experimental treatments regarding protein intake criterion. The fish fed T4, which differed significantly from the different treatments, had the highest level of protein retention, according to the results. Compared to the standard diet, the amount of ether extract in the edible portion was positively lowered upon adding both forms of organic chromium. As mentioned earlier, the findings demonstrate that adding both forms of organic chromium improved growth, food utilization, protein sedimentation, protein productive value, and the reduction of fat percentage in the edible portion.